Low dielectric constant silica-containing cross-linked organic-inorganic materials based on fluorinated poly(arylene ether)s. (21st November 2018) - Tkachenko, Ihor; Kononevich, Yuriy; Kobzar, Yaroslav; Purikova, Olha; Yakovlev, Yurii; Khalakhan, Ivan; Muzafarov, Aziz; Shevchenko, Valery
Abstract: In this work, for the first time, we describe the design and synthesis of novel fluorinated poly(arylene ether)/silica cross-linked materials (FPAE/SiO1.5 ) through a sol-gel process by using the triethoxysilyl-containing fluorinated polyethers as precursors for both organic and inorganic networks formation. The polyether-based precursors with the sol-gel active species were synthesized via hydrosilylation reaction between triethoxysilane and the corresponding allyl-functionalized FPAE under Pt catalysis. Herein, we present two approaches of hydrolysis triethoxysilane groups to silanol ones within sol-gel chemistry: (1) hydrolysis with air moisture and (2) hydrolysis of the ethoxysilyl groups at the interface between two liquids. The mechanical and thermal properties of the FPAE/SiO1.5 materials were studied depending on the structure of macromolecular chains and synthetic route. Scanning electron and atomic force microscopies were employed to investigate the morphology of the resulting silica-containing cross-linked materials. The resulting FPAE/SiO1.5 films were flexible and tough with tensile strength above 25 МPа, and exhibited high thermal stability, having the initial decomposition temperature about 300°С. For more detailed explanation of the thermophysical behavior of the FPAE/SiO1.5 materials, the synthesis method of new silica-containing organic-inorganic system was developed by the direct hydrosilylation reaction between allyl-functionalized polyethers and 1, 1, 3, 3-tetramethyldisiloxane. All films exhibited high hydrophobic properties (water contact angles above 102°), low dielectric constants and losses at room temperature. In particular, the FPAE/SiO1.5 film prepared from tetrafluorobenzene-based polyether showed the ultra-low dielectric constant of 1.86 at 10 kHz. This makes the obtained polymer FPAE/SiO1.5 materials attractive for microelectronics and many other emerging applications. Graphical abstract: Highlights: Novel fluorinated poly(arylene ether)/silica-based materials are prepared through a sol-gel process. Two approaches of hydrolysis triethoxysilane groups to silanol ones within sol-gel chemistry are developed. New silica-containing organic-inorganic system by the direct hydrosilylation reaction are synthesized. The polymers exhibit excellent thermal and mechanical stability, high hydrophobicity, and low dielectric constants.